Analisis Kesalahan Pemahaman Kemampuan Menulis Tata Bahasa Inggris pada Materi ‘To Be’ dan ‘To Do’ Siswa Menggunakan Instrumen Cloze test - Arisa Dias P, Berlianti; Ani Rusilowati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In this era of information and globalization, English has become a very importantlanguage. However, to master English, it is necessary to understand the fouraspects of English language skills consists of 4 main elements, namely reading,writing, speaking, and listening. Reading and listening include understanding orinput while speaking and writing include the product or output of the English learningprocess. Writing is a difficult skill to learn, because writing should understandinggrammar. Mastery of grammar is one of the important aspects in learning English,especially in writing skills. One of the common obstacles experienced by studentsis the auxiliary verbs such as 'to be' and 'to do'. This encourages researchers to findout the errors by students and the factors that became the cause of students' errorsin using 'to be' and 'to do'. Researchers also use cloze test as the instrument.